STUDENTS’ APPROACH TOWARDS BLENDED LEARNING: A COMPARATIVE ANALYSIS - Chowdhury, Suvashree Roy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Blended learning is a novel concept that supports both the offline and online learning. This system of learning amalgamates the traditional method and ICT (Information and Communication) teaching and learning. This mode of teaching and learning espouses both the chalk and blackboard method of disbursing knowledge as well as computers and virtual platforms. Blended learning is a well-established and versatile educational approach. This mode of learning and teaching combines traditional in-person learning with online components. It includes both face-to-face classroom sessions and supplements these with online learning materials. This combination enhances learner engagement across a spectrum of learning styles (Claned, 2023). This present study targets to find out undergraduates’ approach towards blended learning. Some demographics have also been undertaken. Objective: The study objectives was to find out significant differences among undergraduates in relation to certain demographic aspects. Hypotheses: as per the objective Null hypotheses were prepared. Research Design: The study followed a descriptive survey research design. Statistics: As per suitability both inferential and descriptive statistics were applied. Result: A gender difference was noticed in terms of approach towards blended learning. However, result outcome also revealed other aspects of approach towards blended learning. Inferences could be drawn about the attitude of the undergraduates from other statistical result outcome in this study.